تأثير نظام الحوافز على أداء العاملين - نورة, طراد (University of eloued جامعة الوادي, 2020)
"هدفت الدراسة إلى التعريف بنظام الحوافز ومدى فاعلية تأثيره على أداء العاملين حيث تعتبر الحوافز دافع لتحسين أداء العاملين وزيادة كفاءاتهم, حيث قدمنا تعريفات عامة حول الحوافز ونظام الحوافز وأداء العاملين. وتطرقنا في الجانب التطبيقي إلى دراسة الحوافز وتأثيره على أداء العاملين في المؤسسة الإستشفائية المتخصصة مستشفى الأم والطفل بتقرت و قمنا بتعريف للمؤسسة وطبيعة نشاطها. و أظهرت النتائج أن للحوافز المادية ولظروف العمل المتوفرة في المؤسسة تأثيرا إيجابيا على أداء العمل وذلك بسبب إهتمام الحكومة مؤخرا جراء الوباء كورونا / كوفيد 19 تشجيعا لعمال قطاع الصحة. و أوصت الدراسة على ضرورة المحافظ على السياسة المتبعة في الحوافز المادية وظروف العمل وتحسينها حيث أن هناك رضى عام عليها من أجل إشباع حاجات العاملين ويجب إعادة النظر في الحوافز المعنوية والإجتماعية. "" The study aimed to introduce the incentive system and how effective it affects the performance of employees, as incentives are a motivation to improve the performance of employees and increase their competencies. We provided general definitions of incentives, incentives system and the performance of employee , On the practical side, we dealt with the study of incentives and their impact on the performance of the employees of the specialized hospital institution, the Mother and Child Hospital, and we defined the institution and the nature of its activities. The results showed that the material incentives and work conditions available in the institution have a positive impact on work performance, due to the government's recent interest in the Corona / Covid 19 epidemic to encourage workers in the health sector. The study recommended the necessity of preserving and improving the policy followed in material incentives and working conditions, as there is general satisfaction with it in order to follow the needs of workers, and the incorporeity and social incentives must be reconsidered and places the provision of for workers' rest. "
مذكرة ماستر
Keywords: الحوافز , نظام الحوافز, أداء العاملين.; incentives.incentive system.,the performance of employees.